Determinants of household saving in Australia - Harris, Mark; Loundes, J.; Webster, E. (ECONOMIC SOC OF AUSTRALIA BROWN PRIOR ANDERSON PTY LTD, 2002)
This paper uses a unique survey of consumers to test several separate but inter-related hypotheses of household saving. Unit records from 17,585 Australian households are available, which enables the incorporation of a range of household characteristics that may be important factors for saving behaviour, but which are not typically available to researchers undertaking macroeconomic analyses. An ordered probit estimation method is used, and the results support the view that current incomes are perhaps the most important determinant of saving. However, it can also be seen that demographics and householders level of economic optimism play a key role.